Assessment of food allergies in patients under two years of age with skin manifestations referred to pediatric immunology and allergy outpatient clinic - Ünsal, Hilal; Akalin Ertürk, Beyza (The European Research Journal, 2025)
Objectives: In the first two years of life, patients with cutaneous manifestations with suspicion of food allergy are frequently referred to clinicians in daily practice. The aim of this study was to investigate the frequency of food allergy (FA) in infants presenting with cutaneous manifestations. Methods: Patients aged